Evaluasi Pelaksanaan Program 1000 Hari Pertama Kehidupan (HPK) pada Puskesmas Bangkonol Desa Setra Jaya, Kabupaten Pandeglang - Fitri; Handayani, Riny; Rahayu, Sierfi (Epistemik: Indonesian Journal of Social and Political Science, 2025)
The First Thousand Days of Life Movement Program is a program created by the government of Pandeglang district in an effort to accelerate the reduction of stunting. The first thousand days of life Movement program has been implemented since 2019 and is still running to this day. The aim of this study is to find out how the Evaluation of the First Thousand Days of Life Movement Programme in dealing with stunts on the Puskesmas Technical Implementation Unit of Bangkonol in the village of Setrajaya district of Pandeglang. The theory used is the theory of public policy evaluation according to Leo Agustino (2022:84). This research uses descriptive methods of qualitative approach. The results of this study show that the Evaluation of the First Thousand Days of Life Movement Programme in Combating Stunts on the Puskesmas Technical Implementation Unit of Bangkonol in the village of Setrajaya district of Pandeglang has not been performed optimally. With the results obtained on the resource aspects of the apparatus there are no prerequisites in the election of candidates posyandu cadres, there is no monitoring or socialization of the provision of MP-ASI to parents who have young people aged 6-24 months. The institutional aspect of the absence of SOP implementation of the movement program of the first thousand days of life. Prasarana and technology are running to the maximum according to the Ministry of Health in posyandu activities as well as using social media to provide information related to stunting. The finances are well planned and well balanced. The regulation has not yet worked with harmony yet has not received full support from the young parents in the exploitation of posyandu. Keywords: Public Policy Evaluation, The First Thousand Days of Life Movement Programme, Stunting.